TTI-110025 spray tip drops spectrum under different working pressures - Ribeiro, Jackson Roberto Dias; Ribeiro, Luis Felipe Oliveira; Santos, Thales Gomes dos; Nunes, João Guilherme Pereira; Ribeiro Júnior, Marconi Furtado; Vitória, Edney Leandro da (Brazilian Journal of Production Engineering, 2023)
Hydraulic nozzles with air induction are widely used in spray applications, mainly because they reduce the effect of primary drift. However, there are still questions about the behavior of the droplet spectrum at certain pressures. The objective of this work was to analyze the droplet spectrum of the TTI 110025 air induction tip subjected to different working pressures by means of a laser particle analyzer in a protected environment. The experiment was conducted in a completely randomized design (DIC), represented by the pressures 200, 300, 400, 500 and 600 kPa, with four replications. The technical variables analyzed were Dv0.1, DMV, Dv0.9, AR, %V < 100 μm and %V > 500 μm. The TTI 110025 tip showed better results due to the decrease in variables Dv0.1, DMV, Dv0.9 and % V > 500 μm as the working pressure increased. The low value of the variable % V < 100 μm indicated a low risk of drift and the high value % V > 500 μm indicated a high potential for runoff in post-emergence applications. It is suggested to operate the TTI 110025 tip at a pressure of 600 kPa.